"Noise Factory": A qualitative study exploring healthcare providers' perceptions of noise in the intensive care unit. (April 2021) - Kebapcı, Ayda; Güner, Perihan
Abstract: Objectives: This study aimed to explore healthcare providers' perceptions of noise in the intensive care unit. Design: A qualitative exploratory study was conducted using group interviews. Setting: The setting comprised a total of 15 participants (five physicians and ten registered nurses) working in an 18-bed medical surgical intensive care unit at a teaching hospital in Istanbul, Turkey. Semi-structured questions were formulated and used in focus group interviews, after which the recorded interviews were transcribed by the researchers. Thematic analysis was used to identify significant statements and initial codes. Findings: Four themes were identified: the meaning of noise, sources of noise, effects of noise and prevention and management of noise. It was found that noise was an inevitable feature of the intensive care unit. The most common sources of noise were human-induced. It was also determined that device-induced noise, such as alarms, did not produce a lot of noise; however, when staff were late in responding, the sound transformed into noise. Furthermore, it was observed that efforts to decrease noise levels taken by staff had only a momentary effect, changing nothing in the long term because the entire team failed to implement any initiatives consistently. The majority of nurses stated that they were now becoming insensitive to the noise due to the constant exposure to device-induced noise. Conclusion: The data obtained from this study showed that especially human-induced noise threatened healthcare providers' cognitive task functions, concentration and job performance, impaired communication and negatively affected patient safety. In addition, it was determined that any precautions taken to reduce noise were not fully effective. A team approach should be used in managing noise in intensive care units with better awareness.